2010
DOI: 10.3109/15563650.2010.506877
|View full text |Cite
|
Sign up to set email alerts
|

Management of phosgene-induced acute lung injury

Abstract: The mechanisms underlying the phosgene-induced acute lung injury are not well understood. Future experimental work should ensure that potential treatments are tested in a large animal model using realistic dosing regimens and clinically relevant timings, such as those that might be found in a mass casualty situation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
53
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(53 citation statements)
references
References 67 publications
0
53
0
Order By: Relevance
“…This mechanism causes extreme oxidative damage and quickly depletes glutathione stores, worsening the free radical damage. Multiple animal studies and human case reports have shown an increase in vascular permeability, alveolar leakage, and development of pulmonary edema [5][6][7]. Animal models have demonstrated that the pulmonary edema is the result of increased permeability of the alveolar membrane [8].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This mechanism causes extreme oxidative damage and quickly depletes glutathione stores, worsening the free radical damage. Multiple animal studies and human case reports have shown an increase in vascular permeability, alveolar leakage, and development of pulmonary edema [5][6][7]. Animal models have demonstrated that the pulmonary edema is the result of increased permeability of the alveolar membrane [8].…”
Section: Discussionmentioning
confidence: 99%
“…The second and likely more harmful mechanisms by which phosgene causes its effects is through acylation. By this mechanism, phosgene reacts with hydroxyl, thiol, amine, and sulfhydryl groups on proteins, carbohydrates, and lipids [5,6]. This mechanism causes extreme oxidative damage and quickly depletes glutathione stores, worsening the free radical damage.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosgene is a weak topical irritant to the eyes and upper respiratory tract, but, because phosgene readily penetrates into the alveolar region of the lung, it is a strong inducer of severe pulmonary edema, respiratory distress, hypoxia, and death due to respiratory failure (36,37). The onset of pulmonary edema can be delayed and often follows a symptom-free period (37). Phosgene was used as a chemical warfare agent in World War I (38).…”
mentioning
confidence: 99%